Case reportNeuro-folliculo-sebaceous cystic hamartoma is a unique entity - Samaka, Rehab Monir; Alrahabi, Nasser (Polish Journal of Pathology, 2015)
Folliculosebaceous cystic hamartoma (FSCH) is a distinct type of cutaneous hamartoma of pilosebaceous origin that usually occurs on the face. For FSCH, other parts have been reported such as the genital area, and the trunk. A 50-year-old woman presented with an asymptomatic dome-shaped scalp nodule. The clinical diagnosis was pilar cyst or tumor. Histopathological assessment showed FSCH with absolute neural component as the only mesenchymal stroma, leading to the diagnosis of folliculosebaceous cystic neural hamartoma. To the best of our knowledge, absolute neural stroma in FSCH has not been reported previously in the literature.